Lipolytic bacteria isolated from Indonesian sticky rice cake wajik and jenang experiencing with rancidity - ARI SUSILOWATI; SITI LUSI ARUM SARI; RATNA SETYANINGSIH; HANI’A NUR MUTHMAINNA; HAYYU HANDARWATI; ARTINI PANGASTUTI; TJAHJADI PURWOKO (Biodiversitas Journal of Biological Diversity, 2018)
Susilowati A, Sari SLA, Setyaningsih R, Muthmainna HN, Handarwati H, Pangastuti A, Purwoko T. 2018. Lipolytic bacteria isolated from Indonesian sticky rice cake wajik and jenang experiencing with rancidity. Biodiversitas 19: 351-356. Lipolytic bacteria are lipase producing bacteria. These bacteria can be isolated from various sources such as vegetable oil wastes, industrial dairy products, oil-contaminated soil, seeds, and foods containing fat. The lipolytic bacteria were isolated from wajik, jenang manten and jenang alot that have been cultured for 4-35 days using minimum media containing MgSO4.7H2O 0.03%, K2HPO4 0.005%, (NH4) SO40.5% (w/v) supplemented with olive oil as a carbon source. Lipolytic activity was marked by orange luminescence when it was exposed to UV light at 350 nm on colonies grown on media containing olive oil-rhodamine B. Lipolytic bacteria were identified based on colony morphology, cell morphology and sequences of 16S rRNA gene. The 16S rRNA gene sequences were analyzed to determine the identity of bacterial isolates based on the percentage of sequence identity using BLAST Nucleotide software on NCBI website. Results showed there were 7 lipolytic bacteria of 52 isolates. Those bacteria were Gram-negative with spherical and rods shape. The identity of four isolates obtained in wajik indicated 97-98% of similarity to Acinetobacter and one isolate showed 96% of similarity to Pseudomonas. The last two isolates obtained from jenang manten had 99% similarity belonging to the species of Serratia marcescens.